Faithful Participation: The ‘Ulama in Bangladeshi Politics - Islam, Md Nazrul (Politics, religion & ideology, 2022)
The ‘ulama have an important position in Muslim society. They hold influence not only in the socio-religious domain but also in the political domain. This article aims to examine the religio-political roles of the ‘ulama in Bangladesh. The examination has been done through an exhaustive and critical content analysis of published secondary literature about the ‘ulama and politics. The article argues that the Bangladeshi ‘ulama are diverse and have shown their religio-political flexibility throughout recent history. The ‘ulama have also played effective religio-political roles in times of sociopolitical change. Their roles have also varied from time to time in accordance with the sociopolitical conditions. The article also shows that the ‘ulama have gained influence under center-right Governments and lost it under center-left Governments in post-independent Bangladesh.